Population structure in a fungal human pathogen is potentially linked to pathogenicity - E. Anne Hatmaker; Amelia E. Barber; Milton T. Drott; Thomas J. C. Sauters; Adiyantara Gumilang; Ana Alastruey-Izquierdo; Dea Garcia-Hermoso; Justin L. Eagan; Nancy P. Keller; Dimitrios P. Kontoyiannis; Oliver Kurzai; Antonis Rokas (Nature Communications)
Abstract Aspergillus flavus is a clinically and agriculturally important saprotrophic fungus responsible for severe human infections and extensive crop losses. Here, we analyze genomic data from 300 (117 clinical and 183 environmental) A. flavus isolates from 13 countries, including 82 clinical isolates sequenced in this study, to examine population and pan-genome structure and their relationship to pathogenicity. We use single nucleotide polymorphisms to build a phylogeny, analyze admixture, and perform discriminant analysis of principal components. We identify five A. flavus populations, including a new population, D, corresponding to distinct clades in the genome-wide phylogeny. Strikingly, > 75% of clinical isolates were in population D and <5% in population B. We also use orthogroup clustering to identify core and accessory genes within the pan-genome. Accessory genes, including genes within biosynthetic gene clusters, were significantly more common in some populations but rare in others. Our functional annotations show that population D is enriched for genes associated with carbohydrate metabolism, lipid metabolism and certain types of hydrolase activity, whereas a non-clinical population is depleted in genes related to zinc ion binding. In contrast to previous results from the major human pathogen Aspergillus fumigatus, isolation of A. flavus from human specimens is associated with population structure, providing a promising system for future investigations into the contributions of population-specific genetic differences to human infection.